The great white man--eating shark : a cautionary tale - Mahy, Margaret; Allen, Jonathan (New York : Puffin Pied Piper, 1995)
Greedy to have the cove where he swims all to himself, Norvin, who looks a bit like a shark, pretends to be one, scaring off the other swimmers and leaving him in happy aquatic solitude--until he is discovered by an amorous female shark.
2.4
K-3
Keywords: Greed -- Fiction; Sharks -- Fiction